Clinical screening for developmental dysplasia of the hip in Northern Ireland. Issue 7344 (27th April 2002) - Maxwell, S L; Ruiz, A L; Lappin, K J; Cosgrove, A P
Abstract: Problem: The incidence of late diagnosed developmental dysplasia of the hip requiring surgery in Northern Ireland is high. The reported incidence was 1.14 per 1000 children born during 1983-7. Design: Comparative retrospective study. Background and setting: Clinical screening programme in Northern Ireland. Key measure for improvement: Reduced rate of operative intervention in children with developmental dysplasia of the hip detected after 6 months of age. Strategies for change: Increased emphasis on staff training, introduction of a centralised nurse led clinic to improve access to orthopaedic surgeons, and increased use of ultrasonography. Effects of change: The incidence of developmental dysplasia of the hip diagnosed after 6 months in children born between January 1991 and December 1997 fell to 0.59 per 1000, presumably due to improved early detection. Nevertheless, 29 (16%) of the affected hips were not diagnosed when the child was first referred in the first 3 months of life. In addition, for 27 affected hips in children diagnosed after the age of 6 months there was a known risk factor (family history or breech delivery). Lessons learnt: Improvements to screening processes can reduce late incidence of developmental dysplasia of the hip. Further steps to improve detection in children with known risk factors and rate of detection at first referral could reduce late presentation further.